Lung Microvascular Niche, Repair, and Engineering - Tsuchiya, Tomoshi; Doi, Ryoichiro; Obata, Tomohiro; Hatachi, Go; Nagayasu, Takeshi (Frontiers in Bioengineering and Biotechnology, 2020)
Biomaterials have been used for a long time in the field of medicine. Since the success of “tissue engineering” pioneered by Langer and Vacanti in 1993, tissue engineering studies have advanced from simple tissue generation to whole organ generation with three-dimensional reconstruction. Decellularized scaffolds have been widely used in the field of reconstructive surgery because the tissues used to generate decellularized scaffolds can be easily harvested from animals or humans. When a patient’s own cells can be seeded onto decellularized biomaterials, theoretically this will create immunocompatible organs generated from allo- or xeno-organs. The most important aspect of lung tissue engineering is that the delicate three-dimensional structure of the organ is maintained during the tissue engineering process. Therefore, organ decellularization has special advantages for lung tissue engineering where it is essential to maintain the extremely thin basement membrane in the alveoli. Since 2010, there have been many methodological developments in the decellularization and recellularization of lung scaffolds, which includes improvements in the decellularization protocols and the selection and preparation of seeding cells. However, early transplanted engineered lungs terminated in organ failure in a short period. Immature vasculature reconstruction is considered to be the main cause of engineered organ failure. Immature vasculature causes thrombus formation in the engineered lung. Successful reconstruction of a mature vasculature network would be a major breakthrough in achieving success in lung engineering. In order to regenerate the mature vasculature network, we need to remodel the vascular niche, especially the microvasculature, in the organ scaffold. This review highlights the reconstruction of the vascular niche in a decellularized lung scaffold. Because the vascular niche consists of endothelial cells (ECs), pericytes, extracellular matrix (ECM), and the epithelial–endothelial interface, all of which might affect the vascular tight junction (TJ), we discuss ECM composition and reconstruction, the contribution of ECs and perivascular cells, the air–blood barrier (ABB) function, and the effects of physiological factors during the lung microvasculature repair and engineering process. The goal of the present review is to confirm the possibility of success in lung microvascular engineering in whole organ engineering and explore the future direction of the current methodology.